2018
DOI: 10.1055/s-0038-1676564
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tibial Component Alignment and Posterior Slope on Tibial Coverage in a Chinese Population: A Three-dimensional Anthropometric Study

Abstract: The standard for rotational alignment and posterior slope of the tibial component in total knee arthroplasty remains controversial. This study aimed to evaluate the effect of tibial component alignment and posterior slope on tibial coverage. Computer tomographic scans of 101 tibial specimens were used to reconstruct three-dimensional tibia models. A virtual surgery was performed to generate a resection plane with different posterior slopes on the proximal tibia. Symmetrical and anatomical tibial components wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In this modified coordinate system, each of the 3D tibia specimens was repositioned with a standard translation and rotation procedure before the virtual osteotomy. A virtual surgery was then performed on the proximal tibia at a level 8 mm below the lateral tibial plateau with a posterior slope of 7°, which had been found to be a superior slope degree for tibial component placement based on a previous study 20 (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…In this modified coordinate system, each of the 3D tibia specimens was repositioned with a standard translation and rotation procedure before the virtual osteotomy. A virtual surgery was then performed on the proximal tibia at a level 8 mm below the lateral tibial plateau with a posterior slope of 7°, which had been found to be a superior slope degree for tibial component placement based on a previous study 20 (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…In a similar study by Shao et al, cuts were made at 0, 3, 5, and 7 degrees of slope at a resection level different than that in our study, and it was reported that the coverage was increased in both the symmetric and asymmetric components, when the slope angle was increased toward 7 degrees in ideal rotation. 12 However, the resection level was 8 mm below the lateral plateau in the said study. Surgical instruments that targeted 3-mm below the deepest point of the medial plateau were used in our surgical practice, which may account for the result difference between the studies.…”
Section: Discussionmentioning
confidence: 74%
“…6 Asymmetric tibial component designs have been developed; however, these twocomponent types cannot usually prevent overhang from the posteromedial or posterolateral zones during a well-aligned tibial component placement from the mediolateral and anterior aspects of the ideal component rotation. [7][8][9][10][11][12] Therefore, this study aimed to investigate (1) whether the tibial surface area exhibited any changes following tibial plateau cuts at different slope angles, (2) whether there was a change in the compatibility of the symmetric or asymmetric tibial baseplates with the tibial surface or overhang beyond bone margins following cuts at different slope angles, and (3) which slope cut angle could reduce the overhang or underhang. The hypothesis of our study was that during the implantation of the tibial component by providing rotational, mediolateral, and maximum coverage, overhang/underhang that may occur in the posterior cortex of the tibial component can be avoided by using different slope cut angles.…”
mentioning
confidence: 99%
“…30 Other risk factors such as age, BMI, ethnicity, and gender have also been proven to affect proximal tibial morphology, and as such will not necessarily be equally applicable to standardized tibial baseplates. 31,32 Local Tenderness…”
Section: Prevalence Incidence and Size Of Overhangmentioning
confidence: 99%